2015
DOI: 10.1161/hypertensionaha.115.06068
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 Couples Pak1 With the Antihypertrophic Pathway Through the E3 Ubiquitin Ligase, Fbxo32

Abstract: Pathological cardiac hypertrophy is regarded as a critical intermediate step toward the development of heart failure. Many signal transduction cascades are demonstrated to dictate the induction and progression of pathological hypertrophy; however, our understanding in regulatory mechanisms responsible for the suppression of hypertrophy remains limited. In this study, we showed that exacerbated hypertrophy induced by pressure overload in cardiac-deleted Pak1 mice was attributable to a failure to upregulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Previous studies have demonstrated that Smad3 can be phosphorylated by JNK in lung epithelial cells, p38 in breast carcinoma cells or Pak1 in mesangial cells (Chen et al , ; Velden et al , ; Kamaraju and Roberts, ). This is interesting as a lack of Smad3 phosphorylation was also demonstrated in Pak1‐deficient hearts under hypertrophic conditions (Tsui et al , ). This study further confirmed that knockdown of MKK7 or JNK abolished the phenylephrine‐induced phosphorylation of Smad3 despite the presence of Pak1, indicating that Pak1 activation of Smad3 is likely to occur through the MKK7/JNK pathway (Tsui et al , ).…”
Section: Pak1 and The Heartmentioning
confidence: 82%
See 4 more Smart Citations
“…Previous studies have demonstrated that Smad3 can be phosphorylated by JNK in lung epithelial cells, p38 in breast carcinoma cells or Pak1 in mesangial cells (Chen et al , ; Velden et al , ; Kamaraju and Roberts, ). This is interesting as a lack of Smad3 phosphorylation was also demonstrated in Pak1‐deficient hearts under hypertrophic conditions (Tsui et al , ). This study further confirmed that knockdown of MKK7 or JNK abolished the phenylephrine‐induced phosphorylation of Smad3 despite the presence of Pak1, indicating that Pak1 activation of Smad3 is likely to occur through the MKK7/JNK pathway (Tsui et al , ).…”
Section: Pak1 and The Heartmentioning
confidence: 82%
“…This is interesting as a lack of Smad3 phosphorylation was also demonstrated in Pak1‐deficient hearts under hypertrophic conditions (Tsui et al , ). This study further confirmed that knockdown of MKK7 or JNK abolished the phenylephrine‐induced phosphorylation of Smad3 despite the presence of Pak1, indicating that Pak1 activation of Smad3 is likely to occur through the MKK7/JNK pathway (Tsui et al , ). These results highlight the therapeutic potential of Fbxo32 itself and a pharmacological activator of Fbxo32, berberine, has been reported to improve cardiac function (Huang et al , ; Lau et al , ; Zhang et al , ).…”
Section: Pak1 and The Heartmentioning
confidence: 82%
See 3 more Smart Citations